Thermal insulation filling material and steel shell anti-corrosion thermal insulation pipe
By using a thermal filling material containing expanded perlite, mica powder, multiple coated vitrified microbeads and other materials on the steel pipeline, the problems of corrosion and heat loss in steel pipelines during long-term use are solved, and significant thermal insulation effect and corrosion resistance are achieved, extending the service life of the pipeline and reducing energy waste.
Patent Information
- Application Number
- CN202411775837.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-05
AI Technical Summary
Existing steel pipelines face serious corrosion and heat loss problems during long-term use, resulting in shortening of service life, energy waste and environmental pollution. Traditional anti-corrosion and thermal insulation materials have unstable performance in highly corrosive and harsh environments, complex construction and high cost.
Provide a thermal insulation filling material, including main materials, auxiliary materials and additives. The main materials are made of low-thermal materials such as expanded perlite, mica powder, and multiple coated vitrified microbeads. Reinforced materials such as phenolic resin and aluminum silicate fiber are added to the auxiliary materials. The additives contain flame retardants such as aluminum hydroxide and melamine cyanurate. Through ultrasonic dispersion and twin screw extrusion mechanisms, high-performance thermal insulation filling material and steel shell anti-corrosion insulation pipe are formed.
It significantly reduces the thermal conductivity, improves the insulation effect and corrosion resistance, extends the service life of the pipeline, reduces energy waste, and shows excellent stability and safety in highly corrosive and harsh environments.
Smart Images

Figure CN119569400A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat insulation materials, and in particular to a heat insulation filling material and a steel shell anti-corrosion heat insulation pipe. Background Art
[0002] With the acceleration of industrialization and urbanization, pipeline transportation systems have been widely used in energy, chemical, municipal and other fields. Steel pipelines have become one of the main materials for transporting liquids and gases due to their high strength and durability. However, steel pipelines face serious corrosion and heat loss problems during long-term use, which not only affect the service life of the pipelines, but also lead to energy waste and environmental pollution.
[0003] Although traditional anti-corrosion coatings can protect pipelines from corrosion to a certain extent, they are prone to fall off or fail in highly corrosive environments, such as marine environments and chemical plants, leading to increased corrosion of pipelines. Although cathodic protection technology is effective, it has high maintenance costs and is difficult to implement in certain complex environments. Traditional insulation materials such as rock wool and polyurethane foam are prone to aging and deformation during long-term use, resulting in reduced insulation effect and increased energy loss. At the same time, many traditional insulation materials are unstable in harsh environments such as high temperature, low temperature, and humidity, and are prone to losing their original insulation properties. In addition, traditional anti-corrosion and insulation materials require complex processes and technologies during construction, with long construction cycles and high costs. Once the pipeline is corroded or the insulation fails, repair and replacement work is cumbersome and the maintenance cost is high.
[0004] Therefore, there is an urgent need for an insulating filling material and a steel shell anti-corrosion insulating pipe to solve the defects in the prior art, significantly improve the insulation effect and anti-corrosion performance of the steel pipeline, extend the service life of the pipeline, and reduce energy waste. Summary of the invention
[0005] To this end, the present invention provides a thermal insulation filling material and a steel shell anti-corrosion thermal insulation pipe, which solves the problems of high thermal conductivity, insufficient compressive strength and poor flame retardant performance of existing thermal insulation filling materials, and provides a thermal insulation filling material and a steel shell anti-corrosion thermal insulation pipe with comprehensive performance, safety and reliability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] According to a first aspect of the present invention, a thermal insulation filling material is provided, comprising a main material, auxiliary materials and additives, wherein the main material comprises the following raw materials in parts by weight: 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, and 1-3 parts of high temperature resistant chopped glass fibers;
[0008] The auxiliary materials include the following raw materials in parts by weight: 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, and 9-16 parts of slag powder;
[0009] The additive comprises the following raw materials in parts by weight: 4.5-6.5 parts of redispersible latex powder, 0.5-0.8 parts of hydroxypropyl methylcellulose ether, 0.07-0.12 parts of polypropylene fiber, 0.03-0.1 parts of water reducing agent, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate, and 5-10 parts of expanded graphite.
[0010] Furthermore, the method for preparing the multi-coated vitrified microspheres comprises the following steps:
[0011] S1. The vitrified microspheres are first coated with silica with methyl orthosilicate, and then coated with alumina with aluminum nitrate, and then washed, filtered, dried and calcined to finally obtain silica / alumina double-coated vitrified microspheres;
[0012] S2. dissolving n-butyl titanate in an ethanol solution, adding tartaric acid, stirring to form a mixed reaction solution, and then adding double-coated vitrified microspheres, and after solvent thermal treatment, obtaining double-coated vitrified microspheres preliminarily coated with titanium dioxide;
[0013] S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500-600°C for 3-5 hours. After sintering, the microspheres are naturally cooled to room temperature, washed with water, filtered, and dried; the sample is removed, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres;
[0014] The initially sintered titanium dioxide / vitrified microspheres are placed in a tube furnace, the sintering temperature is set to 800-900°C, the sintering time is 4-6 hours, and after the sintering is completed, the titanium dioxide / vitrified microspheres are naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres;
[0015] S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 1.5-3 parts of polydimethylsiloxane, 1.5-3 parts of thioglycolic acid and 0.03-0.15 parts of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
[0016] Furthermore, the specific steps of S1 are as follows:
[0017] (1) Weigh 0.8-1.5 parts of vitrified microspheres, add 7-12 parts of distilled water, mix well to form a slurry, place the slurry in a constant temperature water bath at 55° C., add 0.2-0.3 parts of a 2% surfactant, and stir well for 10-15 minutes to obtain a vitrified microsphere suspension; adjust the pH value of the system to 9-10 with a 10% sodium hydroxide solution, slowly drop 22-30 parts of a 10% methyl orthosilicate solution, and continue to react for 4-8 hours. After the reaction is completed, wash with water, filter, and dry, calcine at 400-600° C. for 2-3 hours, then mix the vitrified microspheres with the sodium hydroxide solution, stir well, heat to 50-60° C., stir for 2-4 hours, then add methyl orthosilicate, continue stirring for 5-8 hours, filter out the treated vitrified microspheres, wash with pure water for 3-5 times, place in an oven, and dry in air to obtain silica-coated vitrified microspheres;
[0018] (2) Add 9-11 parts of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.2-0.3 parts of a 2% surfactant, stir thoroughly for 10-15 minutes to prepare a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 3-7 hours. After the reaction is completed, wash with water, filter, dry, and finally calcine at 450-750°C to obtain silica / alumina double-coated glass microspheres.
[0019] Furthermore, the specific steps of S2 are as follows:
[0020] Dissolve 0.1-0.2 parts of n-butyl titanate in 5-10 parts of anhydrous ethanol, stir evenly, add 0.01-0.02 parts of tartaric acid, continue stirring for 20-40 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 20-40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 180-220°C, perform solvent thermal treatment, maintain the reaction temperature at 180-220°C, and the reaction time is 16-22 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 70-90°C for 10-14 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
[0021] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned thermal insulation filling material, comprising the following steps:
[0022] S1. Weigh 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 55-65 ° C at 200-300 W power for 30-60 min to obtain a main ingredient mixture;
[0023] S2. Weigh 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, 9-16 parts of slag powder, 0.03-0.1 parts of water reducer, sieve and mix in a low-speed mixer, then add 0.03-0.1 parts of water reducer, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate, 5-10 parts of expanded graphite, stir well to form a mixed slurry of auxiliary materials;
[0024] S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture;
[0025] S4. The mixture obtained in S3 is injected into a twin-screw extruder at a screw temperature of 230-240° C. and a screw speed of 500-540 rpm / min to obtain a thermal insulation filling material.
[0026] According to a third aspect of the present invention, there is provided a steel shell anticorrosion insulation pipe, comprising a connection assembly, an insulation layer, a fixing rope, a protective shell and a fixing shell, wherein the insulation layer is made of any one of the above-mentioned insulation filling materials, wherein:
[0027] A connecting component having an outer surface wrapped with thermal insulation;
[0028] A fixing rope, wound around the outside of the thermal insulation layer;
[0029] A protective shell installed outside the fixing rope;
[0030] The fixed shell is sleeved on the outside of the protective shell, and the fixed shell is arranged on the outside of the two protective shells.
[0031] Furthermore, the connection component comprises:
[0032] A pipe body, the outer surface of which is covered with an anti-corrosion coating;
[0033] The limiting collars are arranged in pairs and sleeved on the outside of the tube body. The limiting collars are respectively arranged at both ends of the tube body. The thermal insulation layer is arranged between the two limiting collars. The inner surface of the protective shell is in contact with the outer surface of the limiting collars.
[0034] The protrusion is installed at the end of the pipe body, and the two ends of the protrusion are opposite to form a butt joint pipe body, and the outer side of the butt joint pipe body is covered with the insulation layer.
[0035] Furthermore, the fixed shell is wrapped around the outside of the two ends of the protective shell, the surface of the fixed shell is covered with anti-corrosion paint, and the fixed shell is made of galvanized steel pipe.
[0036] Furthermore, the insulation layer of the insulation pipe includes an insulation coating in addition to the insulation filling material.
[0037] Furthermore, the anti-corrosion coating is a water-based two-component polyurethane-based anti-corrosion coating.
[0038] The present invention has the following advantages:
[0039] 1. The thermal insulation filling material of the present application uses low thermal conductivity materials such as multiple coated vitrified microspheres, expanded perlite and expanded vermiculite silica fume, which significantly reduces the thermal conductivity, effectively reduces the heat transfer and improves the thermal insulation effect; the reasonable formula ratio makes the dry density of the material moderate, which not only ensures the lightweight characteristics but also meets the requirements of structural strength, and is suitable for a variety of construction and industrial applications.
[0040] 2. The thermal insulation filling material of the present application has good compressive strength by adding reinforcing materials such as phenolic resin, aluminum silicate fiber, glass fiber and sulfoaluminate cement, ensuring the structural stability of the material when it is subjected to a large load; and by optimizing the formula and adding polypropylene fiber, the fracture energy of the material is significantly improved, thereby enhancing the material's crack resistance and ductility and improving the overall durability.
[0041] 3. The thermal insulation filling material of the present application is also added with flame retardants such as aluminum hydroxide, melamine cyanurate and expanded graphite, which has excellent flame retardant properties, can effectively prevent the spread of fire, and improve the safety of the material.
[0042] 4. The anti-corrosion and thermal insulation pipe of the present application integrates high-performance anti-corrosion coating and thermal insulation filling materials, which not only provides excellent anti-corrosion performance, but also has excellent thermal insulation effect. This makes the anti-corrosion and thermal insulation pipe suitable for various harsh environments, such as marine engineering, petrochemical, construction and other fields, effectively extending the service life of the pipeline and reducing maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0044] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0045] Figure 1 A three-dimensional diagram of the steel shell anti-corrosion and thermal insulation pipe provided by the present invention;
[0046] Figure 2 A cross-sectional view of the thermal insulation layer provided by the present invention;
[0047] Figure 3 A three-dimensional diagram of the connection assembly provided by the present invention;
[0048] In the figure: 1. Fixed shell; 2. Protective shell; 3. Connecting assembly; 31. Protrusion; 32. Anti-corrosion coating; 33. Pipe body; 34. Limiting ring; 4. Insulation layer; 5. Fixed rope. DETAILED DESCRIPTION
[0049] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] In this document, unless otherwise specified, all percentages, ratios or parts involved are by weight. "Parts by weight" refers to the basic unit of measurement of the weight ratio of multiple components, and 1 part can represent any unit weight, for example, 1 part can be represented as 1g, 1.5g, or 5g, etc.
[0051] The present invention provides a thermal insulation filling material, comprising a main material, auxiliary materials and additives, wherein the main material comprises the following raw materials in parts by weight: 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, and 1-3 parts of high temperature resistant chopped glass fibers;
[0052] The auxiliary materials include the following raw materials in parts by weight: 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, and 9-16 parts of slag powder;
[0053] The additives include the following raw materials in parts by weight: 4.5-6.5 parts of redispersible latex powder, 0.5-0.8 parts of hydroxypropyl methylcellulose ether, 0.07-0.12 parts of polypropylene fiber, 0.03-0.1 parts of water reducing agent, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate and 5-10 parts of expanded graphite.
[0054] Specifically, the preparation method of multi-coated vitrified microspheres includes the following steps:
[0055] S1. The vitrified microspheres are first coated with silica with methyl orthosilicate, and then coated with alumina with aluminum nitrate, and then washed, filtered, dried and calcined to finally obtain silica / alumina double-coated vitrified microspheres;
[0056] S2. dissolving n-butyl titanate in an ethanol solution, adding tartaric acid, stirring to form a mixed reaction solution, and then adding double-coated vitrified microspheres, and after solvent thermal treatment, obtaining double-coated vitrified microspheres preliminarily coated with titanium dioxide;
[0057] S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500-600°C for 3-5 hours. After sintering, the microspheres are naturally cooled to room temperature, washed with water, filtered, and dried; the sample is removed, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres;
[0058] The initially sintered titanium dioxide / vitrified microspheres are placed in a tube furnace, the sintering temperature is set to 800-900°C, the sintering time is 4-6 hours, and after the sintering is completed, the titanium dioxide / vitrified microspheres are naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres;
[0059] S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 1.5-3 parts of polydimethylsiloxane, 1.5-3 parts of thioglycolic acid and 0.03-0.15 parts of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
[0060] Among them, the specific steps of S1 are as follows:
[0061] (1) Weigh 0.8-1.5 parts of vitrified microspheres, add 7-12 parts of distilled water, mix well to form a slurry, place the slurry in a constant temperature water bath at 55°C, add 0.2-0.3 parts of a 2% surfactant, stir well for 10-15 minutes, and prepare a vitrified microsphere suspension; adjust the pH value of the system to 9-10 with 10% sodium hydroxide solution, slowly dropwise add 22-30 parts of 10% methyl orthosilicate solution, continue the reaction for 4-8 hours, and after the reaction is completed , washed with water, filtered, dried, calcined at 400-600°C for 2-3h to obtain silica-coated vitrified microspheres; the vitrified microspheres were mixed with alkali solution, stirred evenly, heated to 50-60°C, stirred for 2-4h, then methyl orthosilicate was added, stirred for 5-8h, the treated vitrified microspheres were filtered out, washed with pure water for 3-5 times, placed in an oven, and dried under air conditions to obtain silica-coated vitrified microspheres;
[0062] (2) Add 9-11 parts of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.2-0.3 parts of a 2% surfactant, stir thoroughly for 10-15 minutes to prepare a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 3-7 hours. After the reaction is completed, wash with water, filter, dry, and finally calcine at 450-750°C to obtain silica / alumina double-coated glass microspheres.
[0063] Among them, the specific steps of S2 are as follows:
[0064] Dissolve 0.1-0.2 parts of n-butyl titanate in 5-10 parts of anhydrous ethanol, stir evenly, add 0.01-0.02 parts of tartaric acid, continue stirring for 20-40 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 20-40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 180-220°C, perform solvent thermal treatment, maintain the reaction temperature at 180-220°C, and the reaction time is 16-22 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 70-90°C for 10-14 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
[0065] The present invention provides a method for preparing the above-mentioned thermal insulation filling material, comprising the following steps:
[0066] S1. Weigh 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 55-65 ° C at 200-300 W power for 30-60 min to obtain a main ingredient mixture;
[0067] S2. Weigh 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, 9-16 parts of slag powder, 0.03-0.1 parts of water reducer, sieve and mix in a low-speed mixer, then add 0.03-0.1 parts of water reducer, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate, 5-10 parts of expanded graphite, stir well to form a mixed slurry of auxiliary materials;
[0068] S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture;
[0069] S4. The mixture obtained in S3 is injected into a twin-screw extruder at a screw temperature of 230-240° C. and a screw speed of 500-540 rpm / min to obtain a thermal insulation filling material.
[0070] The present invention provides a steel shell anti-corrosion thermal insulation pipe, such as Figure 1-3 As shown, it includes a connecting component 3, a heat-insulating layer 4, a fixing rope 5, a protective shell 2 and a fixing shell 1, and the heat-insulating layer 4 is made of the above-mentioned heat-insulating filling material, wherein:
[0071] The connecting component 3 has an outer surface wrapped with a heat-insulating layer 4;
[0072] A fixing rope 5 is wound around the outside of the thermal insulation layer 4;
[0073] A protective housing 2 is mounted outside the fixing rope 5;
[0074] The fixed shell 1 is sleeved on the outside of the protective shell 2 , and the fixed shell 1 is arranged on the outsides of the two protective shells 2 .
[0075] Wherein, the connection component 3 includes:
[0076] The pipe body 33 has an anti-corrosion coating 32 on its outer surface;
[0077] The limiting collars 34 are arranged in pairs and sleeved on the outside of the tube body 33. The limiting collars 34 are respectively arranged at both ends of the tube body 3. The insulation layer 4 is arranged between the two limiting collars 34 to protect the inner surface of the outer shell 2 from being attached to the outer surface of the limiting collars 34.
[0078] The protrusion 31 is installed at the end of the pipe body 33. The two ends of the protrusions 31 are opposite to each other to form a butt-jointed pipe body, and the outer side of the butt-jointed pipe body is covered with a heat-insulating layer 4.
[0079] The fixed shell 1 is wrapped around the outer sides of the ends of the two protective shells 2, the surface of the fixed shell 1 is covered with anti-corrosion paint, and the fixed shell 1 is made of galvanized steel pipe.
[0080] Among them, the insulation layer of the insulation pipe includes insulation coating in addition to insulation filling material.
[0081] Among them, the anti-corrosion coating is a water-based two-component polyurethane-based anti-corrosion coating.
[0082] Specifically, the water-based two-component polyurethane-based anticorrosive coating includes the following components in parts by weight:
[0083] 80-100 parts of water-based two-component polyurethane, 25-35 parts of fluorocarbon resin, 6-9 parts of nano-cerium dioxide, 3-6 parts of nano-silicon dioxide, 3-8 parts of nano-titanium dioxide, 3-5 parts of dispersant, 1.2-2 parts of defoamer, 0.5-1.5 parts of leveling agent;
[0084] The waterborne two-component polyurethane comprises 30-40 parts of waterborne epoxy resin, 20-30 parts of polycarbonate waterborne polyurethane, 25-35 parts of hyperbranched waterborne polyurethane and 10-20 parts of bio-based waterborne polyurethane.
[0085] The dispersant is Disperbyk-161; the defoamer is BYK-088; and the leveling agent is BYK-306.
[0086] Specifically, the coating process of the waterborne two-component polyurethane-based anti-corrosion coating includes the following steps:
[0087] (1) Quantitatively weigh the raw materials of the anti-corrosion coating and set aside;
[0088] (2) adding water-based two-component polyurethane and fluorocarbon resin into a stirring container, stirring at a low speed for 5-10 minutes to ensure that the two resins are initially mixed evenly, adding nano-cerium dioxide, nano-silicon dioxide and nano-graphene in sequence, stirring at a low speed for 5-10 minutes after addition, and then adding dispersant, defoamer and leveling agent in sequence, stirring at a low speed again for 5-10 minutes after addition, and finally transferring the above mixture to a high-speed disperser, setting the speed to 1500-2000rpm, and dispersing for 30-60 minutes to fully mix all the raw materials;
[0089] (3) Ensure that the surface of the substrate is clean, free of oil and dust, check the spraying equipment, and then pour the mixed paint into the spraying equipment to ensure uniform spraying. The spraying thickness is 50-150μm, and 1-5 layers are sprayed. After each layer is sprayed, wait for the previous layer to dry before spraying the next layer;
[0090] (4) After spraying, the sprayed substrate is cured at 60-80° C. for more than 6 hours, and then cured at room temperature for more than 12 hours to obtain a water-based two-component polyurethane-based anti-corrosion coating.
[0091] Example 1
[0092] This embodiment provides a thermal insulation filling material, including a main material, auxiliary materials and additives, wherein the main material includes the following raw materials: 65g of expanded perlite, 9g of mica powder, 12g of multi-coated vitrified microspheres, 4.5g of expanded vermiculite silica fume, and 3g of high temperature resistant chopped glass fiber;
[0093] The auxiliary materials include the following raw materials: 12g phenolic resin, 5g aluminum silicate fiber, 6g glass fiber, 40g sulphoaluminate cement, and 14g slag powder;
[0094] The additives include the following raw materials: 6 g of redispersible latex powder, 0.6 g of hydroxypropyl methylcellulose ether, 0.1 g of polypropylene fiber, 0.06 g of water reducing agent, 25 g of aluminum hydroxide, 6 g of melamine cyanurate, and 8 g of expanded graphite.
[0095] Specifically, the preparation method of multi-coated vitrified microspheres includes the following steps:
[0096] The specific steps of S1 are as follows: (1) weighing 1.2 g of vitrified microspheres, adding 10 g of distilled water, mixing evenly to form a slurry, placing the slurry in a constant temperature water bath at 55° C., adding 0.3 g of a 2% surfactant, and stirring thoroughly for 15 min to obtain a vitrified microsphere suspension; adjusting the pH value of the system to 9-10 with a 10% sodium hydroxide solution, slowly adding 27 g of a 10% methyl orthosilicate solution, and continuing the reaction for 6 h. After the reaction is completed, washing with water, filtering, drying, and calcining at 600° C. for 3 h to obtain silica-coated vitrified microspheres;
[0097] The vitrified microspheres are mixed with the sodium hydroxide solution, stirred evenly, heated to 57°C, stirred for 3 hours, then methyl orthosilicate is added, stirred for 6 hours, the treated vitrified microspheres are filtered out, washed with pure water for 3-5 times, placed in an oven, and dried under air conditions to obtain silica-coated vitrified microspheres;
[0098] (2) Add 10 g of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.3 g of a 2% surfactant, stir thoroughly for 15 min to obtain a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 6 h. After the reaction is completed, wash with water, filter, dry, and finally calcine at 750°C to obtain silica / alumina double-coated glass microspheres.
[0099] The specific steps of S2 are as follows:
[0100] Dissolve 0.15g of n-butyl titanate in 7.5g of anhydrous ethanol, stir evenly, add 0.015g of tartaric acid, continue stirring for 30 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 200°C, perform solvent thermal treatment, maintain the reaction temperature at 220°C, and the reaction time is 19 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 80°C for 12 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
[0101] S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500°C for 4 hours, and after sintering, cooled naturally to room temperature, washed with water, filtered, and dried; the sample is taken out, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres;
[0102] The initially sintered titanium dioxide / vitrified microspheres were placed in a tube furnace, the sintering temperature was set to 800°C, the sintering time was set to 5 hours, and after the sintering was completed, they were naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres;
[0103] S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 2 g of polydimethylsiloxane, 2 g of thioglycolic acid and 0.15 g of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
[0104] This embodiment provides a method for preparing the above-mentioned thermal insulation filling material, comprising the following steps:
[0105] S1. Weigh the expanded perlite, mica powder, multi-coated vitrified microspheres and expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 60 ° C at 300 W power for 45 min to obtain a main ingredient mixture;
[0106] S2. Weigh phenolic resin, aluminum silicate fiber, glass fiber, sulphoaluminate cement, slag powder and water reducer, sieve and mix in a low-speed mixer, then add MasterGlenium SKY, aluminum hydroxide, melamine cyanurate, expanded graphite, stir well to form a mixed slurry of auxiliary materials;
[0107] S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture;
[0108] S4. The mixture obtained in S3 is injected into a twin-screw extruder at a screw temperature of 240° C. and a screw speed of 500 rpm / min to obtain a thermal insulation filling material.
[0109] Specifically, the water-based two-component polyurethane-based anti-corrosion coating covered on the outer surface of the pipe body 33 includes the following components:
[0110] 100g water-based two-component polyurethane, 30g fluorocarbon resin, 8g nano-cerium dioxide, 6g nano-silicon dioxide, 6g nano-titanium dioxide, 5g dispersant, 2g defoamer, 1.5g leveling agent;
[0111] The waterborne two-component polyurethane comprises 40 g of waterborne epoxy resin, 30 g of polycarbonate-type waterborne polyurethane, 30 g of hyperbranched waterborne polyurethane and 20 g of bio-based waterborne polyurethane.
[0112] The dispersant is Disperbyk-161; the defoamer is BYK-088; and the leveling agent is BYK-306.
[0113] Specifically, the coating process of the waterborne two-component polyurethane-based anti-corrosion coating includes the following steps:
[0114] (1) Quantitatively weigh the raw materials of the anti-corrosion coating and set aside;
[0115] (2) adding water-based two-component polyurethane and fluorocarbon resin into a stirring container, stirring at a low speed for 10 minutes to preliminarily mix the two resins, then sequentially adding nano-cerium dioxide, nano-silicon dioxide and nano-graphene, stirring at a low speed for 10 minutes after each addition, then sequentially adding dispersant, defoamer and leveling agent, stirring at a low speed again for 10 minutes after addition, finally transferring the above mixture into a high-speed disperser, setting the speed to 1800 rpm, and dispersing for 45 minutes to fully mix all the raw materials;
[0116] (3) Ensure that the surface of the substrate is clean, free of oil and dust, check the spraying equipment, and then pour the mixed paint into the spraying equipment to ensure uniform spraying. The spraying thickness is 75-100μm, and 2-3 layers are sprayed. After each layer is sprayed, wait for the previous layer to dry before spraying the next layer;
[0117] (4) After spraying, the sprayed substrate is cured at 80° C. for more than 6 hours, and then cured at room temperature for more than 12 hours to obtain a water-based two-component polyurethane-based anti-corrosion coating.
[0118] Example 2
[0119] This embodiment provides a thermal insulation filling material, including a main material, auxiliary materials and additives, wherein the main material includes the following raw materials: 65g of expanded perlite, 9g of mica powder, 10g of multi-coated vitrified microspheres, 4.5g of expanded vermiculite silica fume, and 3g of high temperature resistant chopped glass fiber;
[0120] The auxiliary materials include the following raw materials: 12g phenolic resin, 5g aluminum silicate fiber, 6g glass fiber, 40g sulphoaluminate cement, and 14g slag powder;
[0121] The additives include the following raw materials: 6 g of redispersible latex powder, 0.6 g of hydroxypropyl methylcellulose ether, 0.1 g of polypropylene fiber, 0.06 g of water reducing agent, 25 g of aluminum hydroxide, 6 g of melamine cyanurate, and 8 g of expanded graphite.
[0122] Specifically, the preparation method of multi-coated vitrified microspheres includes the following steps:
[0123] The specific steps of S1 are as follows: (1) weighing 1.2 g of vitrified microspheres, adding 10 g of distilled water, mixing evenly to form a slurry, placing the slurry in a constant temperature water bath at 55° C., adding 0.3 g of a 2% surfactant, and stirring thoroughly for 15 min to obtain a vitrified microsphere suspension; adjusting the pH value of the system to 9-10 with a 10% sodium hydroxide solution, slowly adding 27 g of a 10% methyl orthosilicate solution, and continuing the reaction for 6 h. After the reaction is completed, washing with water, filtering, drying, and calcining at 600° C. for 3 h to obtain silica-coated vitrified microspheres;
[0124] The vitrified microspheres are mixed with the sodium hydroxide solution, stirred evenly, heated to 57°C, stirred for 3 hours, then methyl orthosilicate is added, stirred for 6 hours, the treated vitrified microspheres are filtered out, washed with pure water for 3-5 times, placed in an oven, and dried under air conditions to obtain silica-coated vitrified microspheres;
[0125] (2) Add 10 g of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.3 g of a 2% surfactant, stir thoroughly for 15 min to obtain a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 6 h. After the reaction is completed, wash with water, filter, dry, and finally calcine at 750°C to obtain silica / alumina double-coated glass microspheres.
[0126] The specific steps of S2 are as follows:
[0127] Dissolve 0.15g of n-butyl titanate in 7.5g of anhydrous ethanol, stir evenly, add 0.015g of tartaric acid, continue stirring for 30 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 200°C, perform solvent thermal treatment, maintain the reaction temperature at 220°C, and the reaction time is 19 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 80°C for 12 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
[0128] S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500°C for 4 hours, and after sintering, cooled naturally to room temperature, washed with water, filtered, and dried; the sample is taken out, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres;
[0129] The initially sintered titanium dioxide / vitrified microspheres were placed in a tube furnace, the sintering temperature was set to 800°C, the sintering time was set to 5 hours, and after the sintering was completed, they were naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres;
[0130] S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 2 g of polydimethylsiloxane, 2 g of thioglycolic acid and 0.15 g of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
[0131] This embodiment provides a method for preparing the above-mentioned thermal insulation filling material, comprising the following steps:
[0132] S1. Weigh the expanded perlite, mica powder, multi-coated vitrified microspheres and expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 60 ° C at 300 W power for 45 min to obtain a main ingredient mixture;
[0133] S2. Weigh phenolic resin, aluminum silicate fiber, glass fiber, sulphoaluminate cement, slag powder and water reducer, sieve and mix in a low-speed mixer, then add MasterGlenium SKY, aluminum hydroxide, melamine cyanurate, expanded graphite, stir well to form a mixed slurry of auxiliary materials;
[0134] S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture;
[0135] S4. The mixture obtained in S3 is injected into a twin-screw extruder at a screw temperature of 240° C. and a screw speed of 500 rpm / min to obtain a thermal insulation filling material.
[0136] Specifically, the water-based two-component polyurethane-based anti-corrosion coating covered on the outer surface of the pipe body 33 includes the following components:
[0137] 90g water-based two-component polyurethane, 30g fluorocarbon resin, 8g nano-cerium dioxide, 6g nano-silicon dioxide, 6g nano-titanium dioxide, 5g dispersant, 2g defoamer, 1.5g leveling agent;
[0138] The waterborne two-component polyurethane comprises 40 g of waterborne epoxy resin, 30 g of polycarbonate-type waterborne polyurethane, 30 g of hyperbranched waterborne polyurethane and 20 g of bio-based waterborne polyurethane.
[0139] The dispersant is Disperbyk-161; the defoamer is BYK-088; and the leveling agent is BYK-306.
[0140] Specifically, the coating process of the waterborne two-component polyurethane-based anti-corrosion coating includes the following steps:
[0141] (1) Quantitatively weigh the raw materials of the anti-corrosion coating and set aside;
[0142] (2) adding water-based two-component polyurethane and fluorocarbon resin into a stirring container, stirring at a low speed for 10 minutes to preliminarily mix the two resins, then sequentially adding nano-cerium dioxide, nano-silicon dioxide and nano-graphene, stirring at a low speed for 10 minutes after each addition, then sequentially adding dispersant, defoamer and leveling agent, stirring at a low speed again for 10 minutes after addition, finally transferring the above mixture into a high-speed disperser, setting the speed to 1800 rpm, and dispersing for 45 minutes to fully mix all the raw materials;
[0143] (3) Ensure that the surface of the substrate is clean, free of oil and dust, check the spraying equipment, and then pour the mixed paint into the spraying equipment to ensure uniform spraying. The spraying thickness is 75-100μm, and 2-3 layers are sprayed. After each layer is sprayed, wait for the previous layer to dry before spraying the next layer;
[0144] (4) After spraying, the sprayed substrate is cured at 80° C. for more than 6 hours, and then cured at room temperature for more than 12 hours to obtain a water-based two-component polyurethane-based anti-corrosion coating.
[0145] Example 3
[0146] This embodiment provides a thermal insulation filling material, including a main material, auxiliary materials and additives, wherein the main material includes the following raw materials: 65g of expanded perlite, 9g of mica powder, 8g of multi-coated vitrified microspheres, 4.5g of expanded vermiculite silica fume, and 3g of high temperature resistant chopped glass fiber;
[0147] The auxiliary materials include the following raw materials: 12g phenolic resin, 5g aluminum silicate fiber, 6g glass fiber, 40g sulphoaluminate cement, and 14g slag powder;
[0148] The additives include the following raw materials: 6 g of redispersible latex powder, 0.6 g of hydroxypropyl methylcellulose ether, 0.1 g of polypropylene fiber, 0.06 g of water reducing agent, 25 g of aluminum hydroxide, 6 g of melamine cyanurate, and 8 g of expanded graphite.
[0149] Specifically, the preparation method of multi-coated vitrified microspheres includes the following steps:
[0150] The specific steps of S1 are as follows: (1) weighing 1.2 g of vitrified microspheres, adding 10 g of distilled water, mixing evenly to form a slurry, placing the slurry in a constant temperature water bath at 55° C., adding 0.3 g of a 2% surfactant, and stirring thoroughly for 15 min to obtain a vitrified microsphere suspension; adjusting the pH value of the system to 9-10 with a 10% sodium hydroxide solution, slowly adding 27 g of a 10% methyl orthosilicate solution, and continuing the reaction for 6 h. After the reaction is completed, washing with water, filtering, drying, and calcining at 600° C. for 3 h to obtain silica-coated vitrified microspheres;
[0151] The vitrified microspheres are mixed with the sodium hydroxide solution, stirred evenly, heated to 57°C, stirred for 3 hours, then methyl orthosilicate is added, stirred for 6 hours, the treated vitrified microspheres are filtered out, washed with pure water for 3-5 times, placed in an oven, and dried under air conditions to obtain silica-coated vitrified microspheres;
[0152] (2) Add 10 g of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.3 g of a 2% surfactant, stir thoroughly for 15 min to obtain a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 6 h. After the reaction is completed, wash with water, filter, dry, and finally calcine at 750°C to obtain silica / alumina double-coated glass microspheres.
[0153] The specific steps of S2 are as follows:
[0154] Dissolve 0.15g of n-butyl titanate in 7.5g of anhydrous ethanol, stir evenly, add 0.015g of tartaric acid, continue stirring for 30 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 200°C, perform solvent thermal treatment, maintain the reaction temperature at 220°C, and the reaction time is 19 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 80°C for 12 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
[0155] S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500°C for 4 hours, and after sintering, cooled naturally to room temperature, washed with water, filtered, and dried; the sample is taken out, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres;
[0156] The initially sintered titanium dioxide / vitrified microspheres were placed in a tube furnace, the sintering temperature was set to 800°C, the sintering time was set to 5 hours, and after the sintering was completed, they were naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres;
[0157] S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 2 g of polydimethylsiloxane, 2 g of thioglycolic acid and 0.15 g of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
[0158] This embodiment provides a method for preparing the above-mentioned thermal insulation filling material, comprising the following steps:
[0159] S1. Weigh the expanded perlite, mica powder, multi-coated vitrified microspheres and expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 60 ° C at 300 W power for 45 min to obtain a main ingredient mixture;
[0160] S2. Weigh phenolic resin, aluminum silicate fiber, glass fiber, sulphoaluminate cement, slag powder and water reducer, sieve and mix in a low-speed mixer, then add MasterGlenium SKY, aluminum hydroxide, melamine cyanurate, expanded graphite, stir well to form a mixed slurry of auxiliary materials;
[0161] S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture;
[0162] S4. The mixture obtained in S3 is injected into a twin-screw extruder at a screw temperature of 240° C. and a screw speed of 500 rpm / min to obtain a thermal insulation filling material.
[0163] Specifically, the water-based two-component polyurethane-based anti-corrosion coating covered on the outer surface of the pipe body 33 includes the following components:
[0164] 80g water-based two-component polyurethane, 30g fluorocarbon resin, 8g nano-cerium dioxide, 6g nano-silicon dioxide, 6g nano-titanium dioxide, 5g dispersant, 2g defoamer, 1.5g leveling agent;
[0165] The waterborne two-component polyurethane comprises 40 g of waterborne epoxy resin, 30 g of polycarbonate-type waterborne polyurethane, 30 g of hyperbranched waterborne polyurethane and 20 g of bio-based waterborne polyurethane.
[0166] The dispersant is Disperbyk-161; the defoamer is BYK-088; and the leveling agent is BYK-306.
[0167] Specifically, the coating process of the waterborne two-component polyurethane-based anti-corrosion coating includes the following steps:
[0168] (1) Quantitatively weigh the raw materials of the anti-corrosion coating and set aside;
[0169] (2) adding water-based two-component polyurethane and fluorocarbon resin into a stirring container, stirring at a low speed for 10 minutes to preliminarily mix the two resins, then sequentially adding nano-cerium dioxide, nano-silicon dioxide and nano-graphene, stirring at a low speed for 10 minutes after each addition, then sequentially adding dispersant, defoamer and leveling agent, stirring at a low speed again for 10 minutes after addition, finally transferring the above mixture into a high-speed disperser, setting the speed to 1800 rpm, and dispersing for 45 minutes to fully mix all the raw materials;
[0170] (3) Ensure that the surface of the substrate is clean, free of oil and dust, check the spraying equipment, and then pour the mixed paint into the spraying equipment to ensure uniform spraying. The spraying thickness is 75-100μm, and 2-3 layers are sprayed. After each layer is sprayed, wait for the previous layer to dry before spraying the next layer;
[0171] (4) After spraying, the sprayed substrate is cured at 80° C. for more than 6 hours, and then cured at room temperature for more than 12 hours to obtain a water-based two-component polyurethane-based anti-corrosion coating.
[0172] Comparative Example 1 This example is used as a comparative example of Example 1, in which the multi-coated vitrified microspheres are replaced with ordinary vitrified microspheres, and the other steps and parameters are the same as those of Example 1.
[0173] Comparative Example 2 This example is used as a comparative example of Example 1, except that the multi-coated vitrified microspheres are removed, and the other steps and parameters are the same as those of Example 1.
[0174] Comparative Example 3 This example serves as a comparative example of Example 1, except that the water-based two-component polyurethane is replaced by a common solvent-based polyurethane, and the other steps and parameters are the same as those of Example 1.
[0175] Comparative Example 4 This example is used as a comparative example of Example 1, except that the fluorocarbon resin is replaced by acrylic resin, and the other steps and parameters are the same as those of Example 1.
[0176] Test Example 1:
[0177] In order to more clearly illustrate the present invention, the thermal insulation filling materials in Examples 1-3 of the present invention and Comparative Examples 1-2 were tested according to the method specified in GB / T 20473-2021 "Building Thermal Insulation Mortar" standard, and the dry density, compressive strength, and thermal conductivity of the thermal insulation filling materials were tested; the combustion performance and fracture energy were tested; the test results are as follows:
[0178] Table 1 Various performance tests of the thermal insulation filling materials prepared in Examples 1-3 and Comparative Examples 1-2
[0179]
[0180] Through comprehensive analysis of the performance test results of the thermal insulation filling materials prepared in Examples 1-3 and Comparative Examples 1-2, the following conclusions can be drawn:
[0181] 1. The thermal conductivity of Examples 1-3 ranges from 0.055 W·(m·K) -1 Gradually increase to 0.058W·(m·K) -1 This shows that as the content of multi-coated glass microspheres decreases, the thermal conductivity increases, but still remains at a low level. This shows that multi-coated glass microspheres have a significant positive effect on reducing thermal conductivity and improving the thermal insulation performance of the material. The thermal conductivity of comparative example 1 increased significantly to 0.075 W·(m·K) -1 The thermal insulation performance of ordinary vitrified microspheres is poor, resulting in a significant increase in thermal conductivity. The thermal conductivity of comparative example 2 increased significantly to 0.082 W·(m·K) -1 After removing the multi-coated glass microspheres, the thermal conductivity increased significantly.
[0182] 2. The combustion performance of Examples 1-3 is all A1. The multiple coated glass microspheres significantly improve the combustion performance of the material, giving it a higher fire rating. The combustion performance of Comparative Example 1 is reduced to A2. The fire performance of ordinary glass microspheres is poor, resulting in reduced combustion performance. The combustion performance of Comparative Example 2 is significantly reduced to A12. In the absence of multiple coated glass microspheres, the combustion performance is significantly reduced.
[0183] 3. The change in the amount of multi-coated vitrified microspheres has little effect on the compressive strength, dry density and fracture energy of Examples 1-3. The compressive strength gradually decreases from 1.08 MPa to 1.06 MPa, and the dry density decreases from 298 kg·m -3 Gradually reduced to 297kg·m -3 , the fracture energy is from 366N·m -1 Gradually reduced to 364N·m -1 , all maintained in a relatively high range. The compressive strength, dry density and fracture energy of comparative example 1-2 are lower than those of examples 1-3. This shows that the multi-coated vitrified microspheres play a positive role in improving the mechanical strength, dry density and toughness of the material, while the synergistic effect of other components and preparation processes further optimizes the comprehensive performance of the material.
[0184] In summary, by comparing the data of Examples 1-3 and Comparative Examples 1-2, it can be seen that the multiple coated glass microspheres significantly improve the performance of thermal insulation filling materials, which is specifically manifested in the following aspects: (1) Thermal insulation performance: Multiple coated glass microspheres significantly reduce the thermal conductivity and improve the thermal insulation performance of the material. The thermal conductivity of Comparative Examples 1 and 2 increased significantly, indicating that the thermal insulation performance of ordinary glass microspheres and glass microspheres without multiple coatings is poor. (2) Flame retardant performance: Multiple coated glass microspheres significantly improve the combustion performance of the material, reaching the A1 fire protection standard, and enhancing the safety and reliability of the material. The combustion performance of Comparative Examples 1 and 2 decreased significantly, indicating that the fire protection performance of ordinary glass microspheres and glass microspheres without multiple coatings is poor. (3) The compressive strength and dry density of Examples 1-3 are maintained at a high level. At the same time, the multiple coated glass microspheres significantly improve the fracture energy of the material and enhance the toughness and crack resistance of the material. This shows that the synergistic effect of multi-coated glass microspheres with other ingredients and preparation processes effectively optimizes the comprehensive performance of the material and improves the overall quality and reliability of the material.
[0185] Test Example 2:
[0186] The steel shell anticorrosion insulation pipes of Examples 1-3 and Comparative Examples 3-4 were immersed in a corrosive solution for 30 days. The composition of the corrosive solution was: 20% sodium hydroxide, 15% diesel, 10% crude oil, and the remainder was highly mineralized formation water. The total mineralization of the highly mineralized formation water was 65,000. The temperature of the corrosive solution was 70°C. The coating was observed after the test, and the results are shown in Table 2.
[0187] Table 2 Performance test of the anticorrosion coating of the steel shell anticorrosion insulation pipe of Examples 1-3 and Comparative Examples 3-4
[0188] Test items Coating status Example 1 The coating is intact and the surface is smooth Example 2 The coating is intact and the surface is smooth Example 3 The coating is intact and the surface is smooth Comparative Example 3 The coating surface is rough and has pits, and the surface loses its gloss Comparative Example 4 The coating surface is rough and has pits, and the surface loses its gloss
[0189] in conclusion:
[0190] Through comprehensive analysis of the test results of the anti-corrosion coating performance of the steel shell anti-corrosion insulation pipes prepared in Examples 1-3 and Comparative Examples 3-4, the following conclusions can be drawn:
[0191] After 30 days of immersion in a highly corrosive environment, the coatings of Examples 1-3 are still intact and have a smooth surface, indicating that the combination of multiple coated glass microspheres and water-based two-component polyurethane-based anti-corrosion coatings has excellent corrosion resistance and stability. The coatings of Comparative Examples 3 and 4 appear rough, pitted, and glossy, indicating that ordinary solvent-based polyurethane and acrylic resins have poor anti-corrosion properties in highly corrosive environments. This shows that the multiple coated glass microspheres and water-based two-component polyurethane-based anti-corrosion coatings in the present technical solution play a key role in the steel shell anti-corrosion insulation pipe, significantly improving the anti-corrosion performance of the material. Specifically, the combination of water-based two-component polyurethane and fluorocarbon resin exhibits excellent corrosion resistance and weather resistance in a highly corrosive environment, and the coating remains intact and has a smooth surface. The combination of multiple coated glass microspheres and water-based two-component polyurethane-based anti-corrosion coatings ensures the integrity and stability of the coating in a highly corrosive environment.
[0192] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A thermal insulation filling material, characterized in that: The invention comprises a main material, auxiliary materials and additives, wherein the main material comprises the following raw materials in parts by weight: 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, and 1-3 parts of high temperature resistant chopped glass fibers; The auxiliary materials include the following raw materials in parts by weight: 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, and 9-16 parts of slag powder; The additive comprises the following raw materials in parts by weight: 4.5-6.5 parts of redispersible latex powder, 0.5-0.8 parts of hydroxypropyl methylcellulose ether, 0.07-0.12 parts of polypropylene fiber, 0.03-0.1 parts of water reducing agent, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate, and 5-10 parts of expanded graphite.
2. The thermal insulation filling material according to claim 1, characterized in that: The method for preparing the multi-coated vitrified microspheres comprises the following steps: S1. The vitrified microspheres are first coated with silica with methyl orthosilicate, and then coated with alumina with aluminum nitrate, and then washed, filtered, dried and calcined to finally obtain silica / alumina double-coated vitrified microspheres; S2. dissolving n-butyl titanate in an ethanol solution, adding tartaric acid, stirring to form a mixed reaction solution, and then adding double-coated vitrified microspheres, and after solvent thermal treatment, obtaining double-coated vitrified microspheres preliminarily coated with titanium dioxide; S3. The double-coated vitrified microspheres preliminarily coated with titanium dioxide are placed in a muffle furnace, sintered at a temperature of 500-600°C for 3-5 hours. After sintering, the microspheres are naturally cooled to room temperature, washed with water, filtered, and dried; the sample is removed, washed with water, and filtered to obtain preliminarily sintered titanium dioxide / vitrified microspheres; The initially sintered titanium dioxide / vitrified microspheres are placed in a tube furnace, the sintering temperature is set to 800-900°C, the sintering time is 4-6 hours, and after the sintering is completed, the titanium dioxide / vitrified microspheres are naturally cooled to room temperature, washed, filtered and dried to obtain the final titanium dioxide / vitrified microspheres; S4. Titanium dioxide / glass microspheres are uniformly dispersed in N,N-dimethylformamide, and then 1.5-3 parts of polydimethylsiloxane, 1.5-3 parts of thioglycolic acid and 0.03-0.15 parts of photoinitiator are added to the mixture for reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, washed with water, filtered and dried to obtain multi-coated glass microspheres.
3. The thermal insulation filling material according to claim 2, characterized in that: The specific steps of S1 are as follows: (1) Weigh 0.8-1.5 parts of vitrified microspheres, add 7-12 parts of distilled water, mix well to form a slurry, place the slurry in a constant temperature water bath at 55° C., add 0.2-0.3 parts of a 2% surfactant, and stir well for 10-15 minutes to obtain a vitrified microsphere suspension; adjust the pH value of the system to 9-10 with a 10% sodium hydroxide solution, slowly drop 22-30 parts of a 10% methyl orthosilicate solution, and continue to react for 4-8 hours. After the reaction is completed, wash with water, filter, and dry, calcine at 400-600° C. for 2-3 hours, then mix the vitrified microspheres with the sodium hydroxide solution, stir well, heat to 50-60° C., stir for 2-4 hours, then add methyl orthosilicate, continue stirring for 5-8 hours, filter out the treated vitrified microspheres, wash with pure water for 3-5 times, place in an oven, and dry in air to obtain silica-coated vitrified microspheres; (2) Add 9-11 parts of distilled water to the silica-coated glass microspheres obtained in step (1) to prepare a slurry, place the slurry in a constant temperature water bath at 75°C, add 0.2-0.3 parts of a 2% surfactant, stir thoroughly for 10-15 minutes to prepare a glass microsphere suspension, and adjust the pH of the system to 2-4 with a 10% hydrochloric acid solution; slowly dropwise add 10% aluminum nitrate solution, and continue the reaction for 3-7 hours. After the reaction is completed, wash with water, filter, dry, and finally calcine at 450-750°C to obtain silica / alumina double-coated glass microspheres.
4. The thermal insulation filling material according to claim 2, characterized in that: The specific steps of S2 are as follows: Dissolve 0.1-0.2 parts of n-butyl titanate in 5-10 parts of anhydrous ethanol, stir evenly, add 0.01-0.02 parts of tartaric acid, continue stirring for 20-40 minutes to form a mixed reaction liquid, add the double-coated vitrified microspheres obtained in S1 to the mixed reaction liquid, continue stirring for 20-40 minutes, transfer the resulting mixture to a reactor lined with polytetrafluoroethylene, seal the reactor, put it into an oven preheated to 180-220°C, perform solvent thermal treatment, maintain the reaction temperature at 180-220°C, and the reaction time is 16-22 hours. After the reaction is completed, cool the reactor to room temperature, take out the product from the reactor, wash it with distilled water for 3-5 times, filter the washed product, and then dry it at 70-90°C for 10-14 hours to obtain double-coated vitrified microspheres initially coated with titanium dioxide.
5. A method for preparing the thermal insulation filling material according to claim 1, characterized in that: The following steps are involved: S1. Weigh 45-75 parts of expanded perlite, 5-10 parts of mica powder, 8-12 parts of multi-coated vitrified microspheres, 2.8-5.3 parts of expanded vermiculite silica fume, mix well, put into an ultrasonic disperser, and ultrasonically disperse at 55-65 ° C at 200-300 W power for 30-60 min to obtain a main ingredient mixture; S2. Weigh 8-14 parts of phenolic resin, 3-6 parts of aluminum silicate fiber, 4.5-7.5 parts of glass fiber, 30-50 parts of sulphoaluminate cement, 9-16 parts of slag powder, 0.03-0.1 parts of water reducer, sieve and mix in a low-speed mixer, then add 0.03-0.1 parts of water reducer, 20-30 parts of aluminum hydroxide, 3-8 parts of melamine cyanurate, 5-10 parts of expanded graphite, stir well to form a mixed slurry of auxiliary materials; S3. The main material mixture obtained in S1 and the auxiliary material mixed slurry obtained in S2 were injected into a double-roll mixer and mixed to obtain a uniform mixture; S4. Inject the mixture obtained in S3 into a twin-screw extruder with a screw temperature of 230-240° C. and a screw speed of 500-540 rpm / min to obtain a thermal insulation filling material.
6. A steel shell anti-corrosion thermal insulation pipe, characterized in that: The invention comprises a connecting assembly (3), a heat-insulating layer (4), a fixing rope (5), a protective shell (2) and a fixing shell (1), wherein the heat-insulating layer (4) is made of the heat-insulating filling material according to any one of claims 1 to 4, wherein: A connecting component (3) having an outer surface wrapped with a heat-insulating layer (4); A fixing rope (5) wound around the outside of the thermal insulation layer (4); A protective shell (2) installed outside the fixing rope (5); The fixed shell (1) is sleeved on the outside of the protective shell (2), and the fixed shell (1) is arranged on the outside of the two protective shells (2).
7. The steel shell anticorrosion thermal insulation pipe according to claim 6, characterized in that: The connection component (3) comprises: A pipe body (33) having an outer surface covered with an anti-corrosion coating (32); The limiting collars (34) are arranged in pairs and sleeved on the outside of the tube body (33). The limiting collars (34) are respectively arranged at both ends of the tube body (33). The thermal insulation layer (4) is arranged between the two limiting collars (34). The inner surface of the protective shell (2) is in contact with the outer surface of the limiting collars (34). The protrusion (31) is installed at the end of the tube body (33), and the two ends of the protrusion (31) are opposite to each other to form a butt joint tube body, and the outer side of the butt joint tube body is covered with the thermal insulation layer (4).
8. The steel shell anticorrosion thermal insulation pipe according to claim 7, characterized in that: The fixed shell (1) is wrapped around the outside of the ends of the two protective shells (2); the surface of the fixed shell (1) is covered with anti-corrosion paint; and the fixed shell (1) is made of a galvanized steel pipe.
9. The steel shell anticorrosion thermal insulation pipe according to claim 7, characterized in that: The insulation layer of the insulation pipe includes insulation coating in addition to insulation filling material.
10. The steel shell anticorrosion thermal insulation pipe according to claim 8, characterized in that: The anti-corrosion coating is a water-based two-component polyurethane-based anti-corrosion coating.
Citation Information
Patent Citations
Method for preparing hollow glass microsphere coating titanium dioxide
CN102002263A
Double-coated hollow glass microbead heat-insulated coating and preparation method thereof
CN102391754A
Interference color glass bead and preparation method thereof
CN102951849A
Thin fire-resistant / flame-retardant paint for tunnel and preparation method thereof
CN103043976A
Production method of waterproof and heat-preservation integrated grouting filling mortar
CN107857541A